Solid Waste Generation And Composition In UNIMAS Cafeterias - Syed Almunir, Bin Mohd Zarak (Universiti Malaysia Sarawak (UNIMAS), 2009)
Solid waste management is very important to conserve environment and the waste generated has potential to be converted to energy. The main objective of the study is to determine the waste generation and composition by cafeterias in Universiti Malaysia Sarawak (UNIMAS). The total estimation of solid waste generate by the whole cafeterias in University malaysia Sarawak is 1059.27 kg per day.